Pendidikan Pencegahan Seksual Anak Usia Dini Melalui Video “Kujaga Diriku” di TK Aisyiyah Bukittinggi - Mariyona, Kartika; Rusdi, Pagdya Haninda Nusantri; Nugrahmi, Mega Ade; Ulfa, Zikni Rahmi Aulia (Jurnal Ilmiah Universitas Batanghari Jambi, 2025)
This research aims to provide knowledge information through animated videos to children at Aisyiyah Kindergarten Bukittinggi. This research method is descriptive qualitative. Data were collected by means of observation, interviews and documentation with 3 (three) informants, namely, school principals, teachers and early childhood children. The data collection technique uses triangulation and is explained using the Miles and Huberman interactive model. The results of this research conclude that the animated video "Kujaga Myself" is sexual prevention education for children that is easy to understand, because the educational representation is interesting, like watching a cartoon film, and contains very useful education.